Pengaruh Disiplin Kerja, Lingkungan Kerja Fisik, dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan PT XYZ - Tiara Ikmalia Agnis; Nur Cahyadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze and test the influence of work discipline, physical work environment, and work experience on employee work productivity at PT XYZ. The research approach used in this study is quantitative. The study involved employees of PT XYZ as respondents, with a sample size of 64 respondents. Data analysis was conducted using descriptive statistics and regression analysis. The results of the study indicate that work discipline has a significant positive influence on employee work productivity. However, the physical work environment does not have a significant influence on work productivity. Work experience, on the other hand, has a significant positive influence on employee work productivity at PT XYZ.